2010
DOI: 10.1007/s00338-010-0666-6
|View full text |Cite
|
Sign up to set email alerts
|

Presence of Symbiodinium spp. in macroalgal microhabitats from the southern Great Barrier Reef

Abstract: Coral reefs are highly dependent on the mutualistic symbiosis between reef-building corals and dinoflagellates from the genus Symbiodinium. These dinoflagellates spend part of their life cycle outside the coral host and in the majority of the cases have to re-infect corals each generation. While considerable insight has been gained about Symbiodinium in corals, little is known about the ecology and biology of Symbiodinium in other reef microhabitats.This study documents Symbiodinium associating with benthic ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 52 publications
0
30
0
Order By: Relevance
“…However, sampling in Kāne'ohe Bay has not detected the presence of C15 cells in the water column in a reef that exhibits approximately 90% P. compressa cover over the last five decades. To our knowledge, the study of Venera-Ponton et al (2010) is the only consistent study that found C15 outside of a host, associated with the macroalgae Hypnea panose at Heron Island, GBR.…”
Section: Discussionmentioning
confidence: 87%
“…However, sampling in Kāne'ohe Bay has not detected the presence of C15 cells in the water column in a reef that exhibits approximately 90% P. compressa cover over the last five decades. To our knowledge, the study of Venera-Ponton et al (2010) is the only consistent study that found C15 outside of a host, associated with the macroalgae Hypnea panose at Heron Island, GBR.…”
Section: Discussionmentioning
confidence: 87%
“…First, nutrient enrichments in Symbiodinium cultures show no direct effects of nitrogen toxicity, common to other marine phytoplankters, and confirming that Symbiodinium thrive under higher nutrient levels [46]. Secondly, free-living (although not per se symbiotic) Symbiodinium have been found in sand or on macro-algae [44,47], both of which are a likely source of dissolved organic and inorganic compounds. Surprisingly, the presence of Symbiodinium on or near CCA surfaces has never been examined.…”
Section: (B) Habitat Selectionmentioning
confidence: 99%
“…However, our understanding of Symbiodinium that occur outside a host (referred to as "free-living") is relatively poor in comparison with those that occur in symbioses . Recently, a number of researchers have investigated the diversity of free-living Symbiodinium in the seawater column, benthic sands, macroalgae, and fish feces in the coral reef environment using culture and genetic techniques (Carlos et al, 1999;Gou et al, 2003;Coffroth et al, 2006;Hirose et al, 2008;Littman et al, 2008;Manning and Gates, 2008;Porto et al, 2008;Venera-Ponton et al, 2010).…”
Section: Introductionmentioning
confidence: 99%